Free and open source software in the new digital public policies in Russia. Issue 1 (2nd January 2021) - Bertran, Marie-Gabrielle
ABSTRACT: During Dmitrij Medvedev's presidency from 2008 to 2012, the Russian government chose to promote the development of a new digital economy, with the idea that it would become a competitive sector and a tool for the external power of the country on the international market. However, in 2013, Edward Snowden's revelations were used by the Russian government to promote the development of a strong and diversified digital industry on the domestic market, as it presumably became necessary to ensure the digital sovereignty of a country dependent on foreign actors especially American public authorities and digital companies. This new strategy brought the Russian authorities to examine new kinds of development and new standards for the domestic digital market, especially regarding its regulatory framework, in order to ensure the technological independence of the country as soon as possible (before 2020, according to the 'State Program for an information society 2010–2020'; and then, before 2030, after the adoption of the 'State Program for an information society 2017–2030'). In this regard, free and open-source software appeared as a practical solution, since open (i.e. publicly readable) code ensures low exploitation costs and the possibility of controlling its functions.